Exploring patient-reported outcomes and morbidity burden of patients with VEXAS syndrome: a scoping reviewResearch in context - Fabio Efficace; Daniela Krepper; Francesco Sparano; Paola Fazi; Maria Teresa Voso; Carmelo Gurnari (EClinicalMedicine)
Summary: Background: VEXAS (vacuoles, E1 enzyme, X-linked, auto-inflammatory, somatic) is a recently discovered syndrome of autoinflammatory origin affecting mainly older patients with a clinical picture encompassing a variety of hematological and rheumatological conditions. We aimed to gather current knowledge on patient-reported outcomes (PRO) and morbidity burden of VEXAS patients. Methods: A scoping review conducted via PubMed (last updated September 2024) identified studies involving VEXAS patients, excluding studies primarily addressing hematologic adverse events or laboratory parameters, with no lower date restriction. A double-review process was applied from screening to data charting. Outcomes included the prevalence of manifestations of VEXAS-related morbidity burden and their aggregated rates, adhering to the PRISMA-ScR guidelines. Findings: Out of 357 records, 31 studies met the inclusion criteria, analyzing 1437 patients. The median study sample size was 40 patients (IQR 16–59). Most studies (96·8%) were non-interventional and mostly conducted in France (38·7%) and the USA (32·3%). The median age at symptom onset was 67 years (IQR 66–68·6). Myelodysplastic syndrome was the most common concomitant disease, present in 93·6% of studies. No studies documenting PROs were identified. Skin and pulmonary involvement were the most frequently reported manifestations, appearing in 100% and 96·8% of studies, respectively. Moreover, skin lesions had the highest median prevalence (83·6%, IQR 76–90), followed by fever (81·2%, IQR 67·5–89) and general constitutional symptoms (76%, IQR 54·8–85·3). All symptoms identified in this review were clinician-reported. Interpretation: Our findings may provide preliminary insights into future PRO assessment strategies for VEXAS syndrome. We also advocate for international concerted efforts for a rapid uptake of PRO evidence-based data that can help inform the development of patient-centric therapies for this rare disease. Funding: This work was supported by AIRC5×1000 call “Metastatic disease: the key unmet need in oncology” to MYNERVA project, #21267 Myeloid Neoplasms Research Venture AIRC. Detailed description is available at http://www.progettoagimm.it.